Teacher Assistance in Developing Health Literacy Education for Elementary Schools in DKI Jakarta - Edwita Edwita; Uswatun Hasanah; Imaningtyas Imaningtyas (Indonesian Journal of Community Service in Education, 2026)
The low level of health literacy and environmental awareness among elementary school students poses a challenge in realizing a healthy lifestyle and strengthening the dimensions of students' graduation profiles. On the other hand, teachers still experience limitations in systematically integrating health literacy into the learning process. This community service activity aims to improve teacher competency in developing a health literacy education model based on Educational Sustainable Development (ESD) to strengthen the dimensions of elementary school students' graduation profiles. The activity was carried out at SDN Tanah Tinggi 01, SDN Tanah Tinggi 05, and SDN Tanah Tinggi 11 in Johar Baru District, DKI Jakarta, targeting teachers and principals. The methods used included counseling and training. Counseling was carried out through material presentation, discussion, and reflection related to the importance of health literacy and a healthy lifestyle. The training focused on developing an ESD-based health literacy education model, preparing lesson plans, and developing health literacy media relevant to the characteristics of elementary school students. The results of the activity showed an increase in teachers' understanding of health literacy, their ability to integrate a healthy lifestyle into learning, and their skills in developing an ESD-based learning model. Therefore, this mentoring activity is effective in increasing teacher capacity to develop learning oriented towards health, sustainability, and strengthening student character.